The MEK inhibitor trametinib is effective in inhibiting the growth of canine oral squamous cell carcinoma - Katt, William P. (Springer Nature, 2025)
Oral tumors are relatively common in dogs, and canine oral squamous cell carcinoma (COSCC) is the most prevalent oral malignancy of epithelial origin. COSCC is locally aggressive with up to 20% of patients showing regional or distant metastasis at the time of diagnosis. The treatment of choice most typically involves wide surgical excision. Although long-term remission is possible, treatments are associated with considerable morbidity and can negatively impact functionality and quality of life. OSCCs have substantial upregulation of the RAS-RAF-MEK-MAPK signaling axis, and we had previously hypothesized that small-molecule inhibitors that target RAS signaling might effectively inhibit tumor growth and progression. Here, we demonstrate that the MEK inhibitor trametinib, an FDA-approved drug for human cancers, substantially inhibits the growth of six COSCC cell lines established from current patient tumor samples. We further show preliminary clinical evidence that the drug is able to cause ~ 40% and ~ 80% tumor regression in two out of four patients with spontaneously occurring COSCC, a partial response according to commonly used RECIST criteria. Given the limited treatment options available and the number of dogs for which standard of care is not acceptable, these preliminary findings provide new hope that more suitable treatment options may soon enter the veterinary clinic.